Early‐stage sugar beet taproot development is characterized by three distinct physiological phases. (1st August 2020) - Jammer, Alexandra; Albacete, Alfonso; Schulz, Britta; Koch, Wolfgang; Weltmeier, Fridtjof; van der Graaff, Eric; Pfeifhofer, Hartwig W.; Roitsch, Thomas G.
Abstract: Despite the agronomic importance of sugar beet ( Beta vulgaris L.), the early‐stage development of its taproot has only been poorly investigated. Thus, the mechanisms that determine growth and sugar accumulation in sugar beet are largely unknown. In the presented study, a physiological characterization of early‐stage sugar beet taproot development was conducted. Activities were analyzed for fourteen key enzymes of carbohydrate metabolism in developing taproots over the first 80 days after sowing. In addition, we performed in situ localizations of selected carbohydrate‐metabolic enzyme activities, anatomical investigations, and quantifications of soluble carbohydrates, hexose phosphates, and phytohormones. Based on the accumulation dynamics of biomass and sucrose, as well as on anatomical parameters, the early phase of taproot development could be subdivided into three stages—prestorage, transition, secondary growth and sucrose accumulation stage—each of which was characterized by distinct metabolic and phytohormonal signatures. The enzyme activity signatures corresponding to these stages were also shown to be robustly reproducible in experiments conducted in two additional locations. The results from this physiological phenotyping approach contribute to the identification of the key regulators of sugar beet taproot development and open up new perspectives for sugar beet crop improvement concerning both physiological marker‐based breeding and biotechnological approaches.